Dietary Administration of L-Carnitine During the Fattening Period of Early Feed Restricted Lambs Modifies Ruminal Fermentation but Does Not Improve Feed Efficiency - Martín, Alba; Giráldez, F. Javier; Cremonesi, Paola; Castiglioni, Bianca; Biscarini, Filippo; Ceciliani, Fabrizio; Santos, Nuria; Andrés, Sonia (Frontiers in Physiology, 2022)
Early feed restriction of lambs may program animals to achieve reduced feed efficiency traits as a consequence of permanent mitochondrial dysfunction. The hypothesis at the background of the present study is that dietary administration of L-Carnitine (a compound that promotes the activation and transportation of fatty acids into the mitochondria) during the fattening period of early feed restricted lambs can: (a) improve the biochemical profile of early feed restricted lambs, (b) improve feed efficiency, (c) modulate the ruminal and intestinal microbiota, and (d) induce changes in the gastrointestinal mucosa, including the immune status. Twenty-two newborn male Merino lambs were raised under natural conditions but separated from the dams for 9 h daily to allow feed restriction during the suckling period. At weaning, lambs were assigned to a control group being fed ad libitum a complete pelleted diet during the fattening phase (CTRL, n = 11), whereas the second group (CARN, n = 11) received the same diet supplemented with 3 g of L-Carnitine/kg diet. The results revealed that even though L-Carnitine was absorbed, feed efficiency was not modified by dietary L-Carnitine during the fattening period (residual feed intake, p > 0.05), whereas ruminal fermentation was improved [total short-chain fatty acids (SCFAs), 113 vs. 154 mmol/l; p = 0.036]. Moreover, a trend toward increased concentration of butyrate in the ileal content (0.568 vs. 1.194 mmol/100 ml SCFA; p = 0.074) was observed. Other effects, such as reduced heart weight, lower levels of markers related to muscle metabolism or damage, improved renal function, and increased ureagenesis, were detected in the CARN group. Limited changes in the microbiota were also detected. These findings suggest that L-Carnitine may improve ruminal fermentation parameters and maintain both the balance of gut microbiota and the health of the animals. However, the improved ruminal fermentation and the consequent greater accumulation of intramuscular fat might have hidden the effects caused by the ability of dietary L-Carnitine to increase fatty acid oxidation at the mitochondrial level. This would explain the lack of effects of L-Carnitine supplementation on feed efficiency and points toward the need of testing lower doses, probably in the context of animals being fed in excess non-protein nitrogen.